2003
DOI: 10.1149/1.1618071
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electrical Properties of MOCVD HfO[sub 2] by Multistep Deposition

Abstract: A multistep metallorganic chemical vapor deposition ͑MOCVD͒ technique of HfO 2 gate dielectric and its electrical properties are reported. This technique involves steps of ''deposition followed by postdeposition annealing'' of HfO 2 in which each step is repeated on the previously deposited and annealed HfO 2 . Our experiment demonstrates significant reduction of gate leakage current after high-temperature annealing for HfO 2 deposited using a multistep deposition technique as compared to conventional single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…RSCE appears to be stronger in the modified, double-layer ALD film (Curve M, Figure 4) prepared by the deposition of half of a target dielectric thickness, followed by a post-deposition anneal (PDA), second deposition, and a final PDA (the double-layer dielectric has the same EOT and physical thickness as the conventional single-layer film). The double-layer film with an intermediate anneal was expected to prevent propagation of voids across the total film thickness and improve film leakage current (6). Apparently more effective contaminant ion diffusion in the double-layer film is attributed to the presence of an internal interface in the bulk of the film.…”
Section: Process-induced Charges In High-k Dielectricmentioning
confidence: 99%
“…RSCE appears to be stronger in the modified, double-layer ALD film (Curve M, Figure 4) prepared by the deposition of half of a target dielectric thickness, followed by a post-deposition anneal (PDA), second deposition, and a final PDA (the double-layer dielectric has the same EOT and physical thickness as the conventional single-layer film). The double-layer film with an intermediate anneal was expected to prevent propagation of voids across the total film thickness and improve film leakage current (6). Apparently more effective contaminant ion diffusion in the double-layer film is attributed to the presence of an internal interface in the bulk of the film.…”
Section: Process-induced Charges In High-k Dielectricmentioning
confidence: 99%
“…for as long as 60 s. Upon the completion of the first PDA, an additional 1 nm layer of HfSiO x was deposited, followed by a second PDA under the same conditions. Because of the densification of the film during the first PDA [80,106], several extra ALD cycles were added to the second deposition step in order to match the final physical thickness of the control sample, which was prepared in a single D&A step.…”
Section: Methodsmentioning
confidence: 99%
“…4.8), indicating a severe GB degradation. A huge negative-I t increase implies that the ultrathin IL beneath a GB is highly susceptible to trap generation as [80] and Yeo et al [106] reported that a high-κ dielectric deposited and annealed in multiple steps was denser than that achieved via a single step. The improvement was attributed to a more efficient removal of impurity (the most common being carbon originated from the precursor used for the atomic layer deposition (ALD) process) from a thinner high-κ film, as was verified by Nabatame et al [78].…”
Section: Local Electronic Properties At High-κ Grain and Grain Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Also different annealing conditions have been proposed for better performance of the HfO 2 gate stack devices[74,75,80]. Bera et al[99] reported that multistep metallorganic chemical vapor deposition (MOCVD) of HfO 2 can suppress the gate leakage current due to the offset of the grain boundaries and the pinholes from one layer to another.On the other hand, the reliability study of HfO 2 gate dielectric is getting more attention by the researchers. McPherson et al[100][101][102] reported that the ultimate breakdown strength (E bd ) of a dielectric material decreases with increasing κ and having a relationship of E bd proportional to κ -1/2 .…”
mentioning
confidence: 99%